World economic recession vs. labour market globalization - Wójcik, D.; Hetmańczuk, A. (Економічний вісник Національного гірничого університету, 2009)
The paper is dealt with evaluation of labour market globalization and global economic recession impacts on Polish economic growth. Trends of labour market changes in EU countries are determined. The role of the government in regulation of economic interactions processes is analyzed. The paper also considers models of globalization on the basis of developing regional systems. Some guidelines are proposed to adapt Polish labour market to new economic conditions. Стаття присвячена оцінці впливу глобалізації і світової кризи на розвиток польської економіки. Визначено тенденції розвитку ринку праці в країнах Європейської спільноти. Проаналізовано роль держави у регулюванні процесів економічної взаємодії. Розглянуто моделі глобалізації на основі утворення регіональних об’єднань. Запропоновано рекомендації для адаптації польського ринку праці до нових економічних умов.